Hubungan Pemberian Program Vaksinasi Dengan Tingkat Kecemasan Pada Masyarakat Saat Pandemic Covid-19 Di Daerah RT 02 Desa Bojong Baru Kabupaten Bogor Tahun 2021 - Raihandika Permana (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
The COVID-19 vaccination program is a new program initiated by the government to create herd immunity for COVID-19 with a target target of 70% of the population. Vaccination turns out to provide its own anxiety for the community. Anxiety occurs during the Covid-19 pandemic and is also felt when there is a vaccination program in the community. To find out the relationship between the vaccination program and the level of anxiety in the community during the Covid-19 pandemic in the Rt. 02 Bojong Baru Village, Bogor Regency in 2021. The type of research used is descriptive correlation research using a cross sectional study approach. Based on the results of the Spearman rank test, there is a correlation or relationship between the administration of the vaccination program and the level in the Rt.